The Impact Of Economic Growth, Innovation And Political Institutions On Carbon Dioxide Emissions In Developing Economies - Khan, Hamad Hasul (2023)
Climate change and global warming have received worldwide attention due to their extensive repercussions. The problem of balancing economic growth and environmental sustainability with limited resources is another important obstacle for governments as the governments may be forced to choose between economic growth and enhancement of environmental quality. However, the literature on economic growth, CO2 emissions, and other related topics has expanded in recent years. Yet, innovation and political institutions are among the most overlooked aspects that have an important impact in relation to CO2 emissions and environmental degradation. In addition, the literature on these topics is either limited or contradictory. As a result, this research aimed to investigate the impact of political institutions, economic growth, FDI inflows, and innovation on CO2 emissions. In addition, the study sought to determine if the Environmental Kuznets Curve (EKC) and pollution haven hypothesis (PHH) hold true for selected developing economies, particularly under the effect of the political institution. This study employed panel ARDL methodology which included mean group (MG), pool mean group (PMG), and dynamic fixed effects (DFE) to achieve short-run and long-run estimates. The study's outcomes confirmed the EKC hypothesis for developing economies and produced conflicting proof of PHH's existence. Additionally, the study revealed that innovation and energy consumption had a beneficial influence on CO2 emissions. In contrast,